Competence-Adaptive Assessment Using IRT for Junior Photographer Qualification - Novrianti Novrianti; Lisa Candra Sari (CV FOUNDAE, 2025)
The rapid evolution of workforce demands necessitates competency-adaptive assessments that align education with industry standards. Traditional methods, often static and norm-referenced, fail to address the dynamic skills required in creative disciplines like photography. This study developed a Competence-Adaptive Assessment (CAA) integrating Item Response Theory (IRT) to enhance validity, and reliability in a photography course. A mixed-methods design was employed, involving 120 undergraduate photography students and six instructors in a 12-week quasi-experimental study. Quantitative results demonstrated significant learning gains (effect size d = 1.12), improved certification pass rates (24% increase), and enhanced technical competencies, particularly in lighting mastery. Qualitative findings revealed that adaptive feedback and personalized pathways increased engagement but also highlighted tensions between automated assessment and creative evaluation. The study contributes a scalable framework for competency-based education in creative fields, though it underscores the need to balance technical precision with artistic freedom. Implications include the potential for CAA to modernize vocational assessments while calling for further refinement to address creative subjectivity